The Effect of Profitability, Company Size and Leverage on Company Value - Oktaviani, Devina; Satriansyah, Arief; Widianingrum, Enggar (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to determine and analyze the effect of profitability, company size, and leverage on company value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2020-2022. The type of research used is statistical quantitative used with a population of 84 companies. A sample of 19 companies was selected through a purposive sampling technique. The independent variables in this study are profitability (ROA), firm size (LN), and leverage (DER) while the dependent variable in this study is the company value (PBV). The results showed that partially, profitability (ROA) and leverage (DER) had a positive and significant effect on firm value (PBV). Meanwhile, firm size (LN) has no significant effect on firm value (PBV). Simultaneously profitability, firm size and leverage have a positive effect on firm value.